Development of an agile development method based on Kanban for distributed part-time teams and an introduction framework - Hofmann, Constantin; Lauber, Sebastian; Haefner, Benjamin; Lanza, Gisela (Procedia manufacturing, 2018)
In the context of Industry 4.0, the development of maintainable and scalable applications becomes a core activity to master for industrial companies. To offer convincing trainings, learning factories have to coordinate the development of IT and hardware solutions with training concepts. The development of maintainable, modular and stable IT solutions in coherence with the hardware is the basis for good trainings. Especially learning factories face the challenge to work with part-time staff that is unfamiliar with large IT and hardware projects, web technology or PLC programming and development methods. In this paper we present a model how to introduce agile methods step-by-step to teams that have to cope with the challenge of a new project paired with a new technology and development methodology without overloading the team. An adapted teaching concept to introduce these development methods has been developed. For each of the maturity levels, tools and processes are presented as well as criteria to indicate when the team is ready to pass to the next level. The paper also presents the results of an application of the model to the development team at the Learning Factory Global Production at wbk.